Impact of obesity on short and long term results following a pancreatico-duodenectomy. (June 2017) - Shamali, Awad; Shelat, Vishal; Jaber, Bashar; Wardak, Aisha; Ahmed, Mohamed; Fontana, Martina; Armstrong, Thomas; Abu Hilal, Mohammed
Abstract: Background: The impact of obesity on short and long term outcomes following a pancreatico-duodenectomy (PD) is still unclear and needs further clarification. Methods: Demographic, operative and outcomes data in 524 patients undergoing PD were analysed. Results: Ninety-seven patients (18.5%) had BMI greater than or equal to 30 kg/m 2 (group A) and 427 patients (81.5%) had BMI less than 30 kg/m 2 (group B). Group A had a significantly greater operative duration, (375 vs 360 min, p = 0.024) and a higher intra-operative blood loss, (660 vs 500 ml, p = 0.005). Post-operative pancreatic fistula (POPF) were more common in Group A (28.9% vs 16.2%, p = 0.006), this difference was also observed when considering only major POPF (Grade B and C) (16.5% vs 8.0%, p = 0.020). Intra-abdominal collections were higher in Group A, 28.9% compared to 19.0% in Group B (p = 0.037). On multivariate analysis BMI (OR 2.006; 95% CI 1.147–4.985, p = 0.040), small pancreatic duct (OR 2.755; 95% CI 1.589–2.968, p = 0.026) and soft pancreas (OR 2.289; 95% CI 1.126–3.665, p = 0.040) were found to be independent factors for POPF. The median survival for adenocarcinomas was 20 months in Group A and 22 months in Group B, (p = 0.109). Conclusion: Patients with BMI ≥ 30 are at an increased risk of developing pancreatic fistula following PD. Obesity does not appear to have an impact on long term outcomes in patients undergoing a PD for adenocarcinomas. Highlights: Obesity is an independent factor for post-operative pancreatic fistula. Obesity does not affect oncological outcomes following Pancreatico-duodenectomy. Obesity is associated with greater operative time and higher intra-operative blood loss.